2022
DOI: 10.2991/assehr.k.220203.039
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between the Intensity of Using Tik Tok Social Media and Stress Level Among Teenagers in Makassar City During the Pandemic

Abstract: The current COVID-19 pandemic requires individuals to keep their distance and maintain their health by doing activities from home, to stay connected to each other, teenagers use various kinds of social media, one of which is tik tok social media. There has been an increase in social media users, especially tik tok, in early 2020 until now. The use of tik tok social media access is carried out excessively for 4-8 hours a day. Excessive use of social media has an impact on stress. For teenagers, this can affect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…This is due to various factors, including high curiosity, fear of missing out on new information or things, and difficulty sleeping due to exposure to blue light from smartphone screens which can interfere with the production of the hormone melatonin which is needed to regulate sleep cycles. Another study by Ismail, Rustham, and Ibrahim (2021) also showed a significant positive relationship between the stress levels of adolescents using the social media platform TikTok. Research by Sa'diyah, Naskiyah and Rosyadi (2022) also shows that the more intensely a person uses social media, the worse his mental health will be.…”
Section: Bivariate Analysismentioning
confidence: 87%
“…This is due to various factors, including high curiosity, fear of missing out on new information or things, and difficulty sleeping due to exposure to blue light from smartphone screens which can interfere with the production of the hormone melatonin which is needed to regulate sleep cycles. Another study by Ismail, Rustham, and Ibrahim (2021) also showed a significant positive relationship between the stress levels of adolescents using the social media platform TikTok. Research by Sa'diyah, Naskiyah and Rosyadi (2022) also shows that the more intensely a person uses social media, the worse his mental health will be.…”
Section: Bivariate Analysismentioning
confidence: 87%
“…This is linear with the research of Mulyani et al (2018) which stated that adolescent girls are used to spending more time on social media than boys. One underlying reason is that adolescent girls like to get attention from others (Ismail et al, 2022). Hartinah et al (2019) argued that a high level of narcissism causes the higher intensity of women in social media than men.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the potential risks that social media may produce, there have also been researches that pinpoint on the TikTok's influences on teenage anxiety. Based on the already revealed risks of social media, Ismail's research was focusing on the correlation between the intensity of using TikTok and stress level among teenage users during the pandemic of COVID-19 [9]. By executing quantitative research in his city towards teens aged 13-20, the results of data analysis conducted in this study indicate that the intensity of using TikTok social media access and stress levels have a significant relationship, alongside a crucial influence on adolescent's development, where adolescents experience many significant changes in their lives to build relationships and socialize with their peers.…”
Section: Literature Reviewmentioning
confidence: 99%